REALITAS KONTEMPORER ISLAM DAN KERAGAMAN AMERIKA SERIKAT DAN KANADA - Harahap, Aziddin (LPPM Universitas Labuhanbatu, 2020)
The history of Islam in the United States dates back to around the 16th century, when EstevÃ¡nico of Azamor was the first Muslim recorded in North American history.1 However, most researchers in studying the arrival of Muslims in the US have focused more on the arrival of immigrants who came from the Middle East in the late 19th century. This migration of Muslims to the US took place over a different period, which is often called the